2015
DOI: 10.1039/c4dt03881a
|View full text |Cite
|
Sign up to set email alerts
|

High temperature neutron diffraction studies of PrInO3and the measures of perovskite structure distortion

Abstract: The crystal structure of PrInO(3) was investigated in the temperature range 303-1123 K by high-resolution neutron-powder diffraction. The PrInO(3) adopts a highly distorted variant of the perovskite structure with the orthorhombic Pnma space group in the whole temperature range investigated. The bond length and bond-angle analysis revealed a very slow tendency to decrease structural distortion with increasing temperature. Comparison of different parameters quantifying perovskite structure distortion calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The lattice parameters are in good agreement with those recently tabulated by Shukla et al, while the fractional coordinates for LaInO 3 match those found in an earlier powder XRD study . Likewise, fractional coordinates for PrInO 3 are close to those from a powder neutron diffraction study, although of course in the current X-ray study, uncertainties in oxygen positions are bigger than in the neutron study.…”
Section: Resultssupporting
confidence: 90%
“…The lattice parameters are in good agreement with those recently tabulated by Shukla et al, while the fractional coordinates for LaInO 3 match those found in an earlier powder XRD study . Likewise, fractional coordinates for PrInO 3 are close to those from a powder neutron diffraction study, although of course in the current X-ray study, uncertainties in oxygen positions are bigger than in the neutron study.…”
Section: Resultssupporting
confidence: 90%
“…where n is the coordination number (in this case n = 6), and d i and d are the individual and average values of the interatomic distances in polyhedra, respectively (Baszczuk et al, 2015). The calculated octahedral distortions versus x (tin content) are shown in Fig.…”
Section: Phase-composition-dependent Structural Properties Of the Btsmentioning
confidence: 99%
“…The crystal structure, BEC and dielectric tensor were computed using the Vienna ab inito simulation package (VASP) [41]. The calculations were performed using the experimental structural parameters obtained at room temperature [43][44]37] for the rhombohedral phase of PAO ( ) 3 R c and the orthorhombic phase of PGO and PIO (Pbnm). For more details on computational parameters, see Section ESI 1 †.…”
Section: Computational Detailsmentioning
confidence: 99%